Novel mutations in NOTCH2 gene in infants with neonatal cholestasis - Eliana Shaul; Debora Kogan-Liberman; Stephanie Schuckalo; Dominique Jan; Michelle Ewart; Trang Nguyen; Mercedes Martinez; Nadia Ovchinsky (MDPI AG, 2019)
One cause of neonatal cholestasis (NC) is paucity of intrahepatic bile ducts which can be associated with Alagille syndrome or non- syndromic. Alagille syndrome is caused by autosomal dominant mutations in the Notch signaling pathway ligand Jagged1 in 94% of patients and mutations in the NOTCH2 receptor in <1% of patients. This is a retrospective case series studying infants with neonatal cholestasis found to have variants of unknown significance (VOUS) in NOTCH2. Sorting intolerant from tolerant (SIFT) and polymorphism phenotyping (PolyPhen) were utilized to predict a damaging effect. Five infants with NC without other features of Alagille syndrome were found to have one copy of a VOUS in NOTCH2, predicted to be damaging by SIFT and PolyPhen. Our cases support the notion that NOTCH2 mutations may result in hypoplastic biliary system. Further characterization of these variants is important to assist with our clinical approach to NC.